Wyjątkowy bałkanizm anatolijskiego pochodzenia - Elwira, Kaczyńska; Witczak, Krzysztof Tomasz (Papers in Linguistics, 2020)
The paper discusses an exceptional balkanism, attested in most Balkan languages, cf. Modern Greek κουμάσι n. ‘kennel (for a dog); hencoop’, dial. (Cretan) κούμος m. ‘id.’; Albanian kumác m. ‘enclosure for small domestic animals: coop, cote; dog kennel; pig pen, sty’ and qyméz m. ‘chicken coop, dovecote’; Aromanian cumás ‘hencoop’; Bulgarian (dial.) кумà ‘antechamber in a country hut’; Turkish kümes ‘poultry-house; coop, hut’, also küm ‘place for domesticated animals’. It is suggested that the above-mentioned bunch of words represents an ancient borrowing from an Anatolian source, cf. Hittite ḫummaš c. ‘stable, stall, sty’, Luwian ḫummati- ‘stable’.